Validation of baking to control Salmonella serovars in hamburger bun manufacturing, and evaluation of Enterococcus faecium ATCC 8459 and Saccharomyces cerevisiae as nonpathogenic surrogates for thermal process validation - Holmgren, Elizabeth Suzanne (Kansas State University, 2015)
With the implementation of the Food and Drug Administration’s Food Safety Modernization Act, the food industry must scientifically verify that current production processes provide sufficient protection against pathogens. This study was conducted to validate a simulated commercial baking process for hamburger buns to control Salmonella spp. contamination and to determine the appropriateness of using non-pathogenic surrogates (Enterococcus faecium ATCC 8459 or Saccharomyces cerevisiae) for in-plant process validation studies. Wheat flour was separately inoculated (~6 log CFU/g) with three Salmonella serovars (Typhimurium, Newport or Senftenberg) or E. faecium. Dough was formed, proofed, and baked to mimic commercial manufacturing conditions. Non-inoculated dough was used to evaluate S. cerevisiae (Baker’s yeast) survival during baking. Buns were baked for 9, 11 and 13 min in a conventional oven set at 218°C, with internal bun temperature profiles recorded. Salmonella serovars and S. cerevisiae were reduced by >6 log[subscript]10 CFU/g after 9 min of baking. E. faecium was detected by direct plating after 11 min of baking but not after 13 min. After 13 min of baking, all three target organisms were eliminated (>6 log CFU/g reduction) in the buns. D- and z-values of Salmonella spp. (3-serovar cocktail), E. faecium, and S. cerevisiae in bun dough were also determined. D-values of Salmonella spp. and E. faecium during heating of dough were 28.64 and 133.33, 7.61 and 55.67, and 3.14 and 14.72 min at 55, 58 and 61°C, respectivly; whereas, D-values of S. cerevisiae were 18.73, 5.67 and 1.03 min at 52, 55 and 58°C, respectivly. The z-values of Salmonella spp., E. faecium and S. cerevisiae were 6.58, 6.25 and 4.74ºC, respectively. E. faecium demonstrated greater thermal resistance than Salmonella spp. and S. cerevisiae, making it an appropriate (and conservative) surrogate to establish thermal process lethality in the validation of commercial baking operations. The low thermal tolerance of S. cerevisiae relative to Salmonella limits its usefulness as a potential surrogate for process validations.
Keywords: Bakery; Validation; Salmonella; Enterococcus faecium; Surrogate; Hamburger bun; Food Science (0359)